(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study analyzes the use of artificial intelligence (AI) to support inclusive education in GCC countries and Yemen and proposes a practical framework to enhance this approach. Using a descriptive-analytical method with surveys, interviews, and document analysis, the findings reveal limited AI application and disparities in policies, infrastructure, and staff awareness. The study presents a proposed model to activate AI in inclusive education, aiming to promote more equitable and accessible learning environments.